Feeling at Home Outdoors: The Courtyard of the Rozes House - García-Casabán, Marta (UI Scholars Hub, 2025)
Although the courtyard was not a central element in the early stages of the Modernist movement, it later became a key transitional space between the interior and the exterior. This concept was reinterpreted in Spain through a balance between modernity and tradition, particularly in holiday homes along the Costa Brava. This research explores the role of the outdoor room in modern Mediterranean architecture and its relationship with the environment, using José Antonio Coderch's Rozes House as a case study. Through redrawing, the text aims to analyse how the 'outdoor room' in Rozes House enhances spatial continuity and strengthens the relationship between architecture, inhabitants, and the landscape. It helps to restore the identity and memory of the place through spatial solutions that respect both the landscape and tradition, reaffirming its power as a catalyst for a fulfilling way of life. As an essential design tool, the outdoor room transforms the domestic space by integrating nature and enriching the inhabitant's experience.